Antibiotics-induced depletion of mice microbiota induces changes in host serotonin biosynthesis and intestinal motility. Issue 1 (December 2017) - Ge, Xiaolong; Ding, Chao; Zhao, Wei; Xu, Lizhi; Tian, Hongliang; Gong, Jianfeng; Zhu, Minsheng; Li, Jieshou; Li, Ning
Abstract Background The gastrointestinal motility is affected by gut microbiota and the relationship between them has become a hot topic. However, mechanisms of microbiota in regulating motility have not been well defined. We thus investigated the effect of microbiota depletion by antibiotics on gastrointestinal motility, colonic serotonin levels, and bile acids metabolism. Methods After 4 weeks with antibiotics treatments, gastrointestinal and colon transit, defecation frequency, water content, and other fecal parameters were measured and analyzed in both wild-type and antibiotics-treated mice, respectively. Contractility of smooth muscle, serotonin levels, and bile acids levels in wild-type and antibiotics-treated mice were also analyzed. Results After antibiotics treatment, the richness and diversity of intestinal microbiota decreased significantly, and the fecal of mice had less output (P  < 0.01), more water content (P  < 0.01), and longer pellet length (P  < 0.01). Antibiotics treatment in mice also resulted in delayed gastrointestinal and colonic motility (P  < 0.05), and inhibition of phasic contractions of longitudinal muscle from isolated proximal colon (P  < 0.01). In antibiotics-treated mice, serotonin, tryptophan hydroxylase 1, and secondary bile acids levels were decreased. Conclusion Gut microbiota play an important role in the regulation of intestinal bile acids and serotonin metabolism, which could probably contribute to the association between gut microbiota and gastrointestinal motility as intermediates.